Interpretable soft computing deep ensemble model for predicting deformation of surrounding rock in deep tunnels - Xuanhao Chen; Rong Fan; Yang Li; Tianxing Ma; Yong Zhong (European Journal of Environmental and Civil Engineering, 2025)

A review of data-driven key technologies for intelligent citrus systems - Wengang Li; Aoting Wan; Jing Li; Kelin Chen; Zifei Ma; Qinghua Li; Rong Jiang; Juan Yang; Tong Li (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Spatial patterns of leaf angle distribution covary with canopy fluorescence yield, reflectance indices, and leaf chlorophyll content, in a mixed temperate forest - Andrew D. Jablonski; Rong Li; Jongmin Kim; Manuel Lerdau; Carmen Petras; Xi Yang (Remote Sensing of Environment, 2025)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Influence of multiple environmental factors on plastics in facility agriculture soils at a national scale, China - Guiming Liu; Sashuang Rong; Cun Liang; Yang Yang; Xuyang Zheng; Shutao Wang; Shiming Su; Zhenyong Li; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

Simulated analog crayfish meat based on 3D print: Effect of crayfish oil emulsion on gel properties of surimi - Xiaofeng Zhan; Shuhui Yang; Weixia Zhou; Yanyan Wang; Jianhua Rong; Youming Liu; Chuan Li; Yongqiang Zhao; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Multidimensional strategy for discovering saltiness-enhancing peptides in shrimp heads integrating ultra-high pressure hydrolysis and machine learning - Na Li; Yafang Song; Yang Liu; Rong Liu; Yahong Li; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

Cholesterol and 24S-OHC Induce Neuronal Apoptosis and Necroptosis, but Not Ferroptosis Despite Elevated Iron Levels - Yinghui Li; Tingbin Xu; Jiahua Yang; Rong Liu; Yan Qu; Jun Wang (Molecular Neurobiology, 2025)

Novel multi-component synergistic bioink that balances biocompatibility and mechanical strength for cartilage regeneration - Zijun Ma; Wendan Jia; Xiaoyuan Wang; Rong Cheng; Lu Han; Meng Li; Xiaoning Yang; Shengbo Sang (Journal of Zhejiang University-SCIENCE B, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

Knockout of the Agrobacterium ILVC gene generates a valine-isoleucine auxotrophic strain for plant transformation - Yanhui Yang; Jun Lu; Tianrui Xue; Zhenli Cao; Mingjie Li; Zhongyi Zhang; Rong Wang; Tongyu Wu (Transgenic Research, 2025)

Achnatherum inebrians tolerance to salt stress is linked with the changes of rhizosphere microbiome and root exudates - Ronggui Liu; Chao Wang; Jie Jin; Xiaoshan Zhu; Lanlan Chen; Yang Yang; Rong Zheng; Kamran Malik; Jianfeng Wang; Chunjie Li (Soil Ecology Letters, 2025)

Correction to: Antler stem cells as a novel stem cell source for reducing liver fibrosis - Xiaoli Rong; Yanyan Yang; Guokun Zhang; Haiying Zhang; Chunyi Li; Yimin Wang (Cell and Tissue Research, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Caulerpin suppresses tumor-associated angiogenesis and tumor growth via Hippo signaling in cervical cancer - Guang Yang; Yan Mo; Honghong Rong; Bihui Guo; Qingbing Zha; Hanli Shuai; Minghua Wang; Ping Li (Toxicology and Applied Pharmacology, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Competitive exclusion of insect parasitic fungi: Enhanced metabolite biosynthesis in Beauveria bassiana and fatty acid production in Metarhizium robertsii during host coinfection - Kexin Liu; Gen Li; Siying Wu; Yang Zhang; Rong Zhou; Cheng Lv; Xingcheng Yue; Zhuoran Zhu; Tianzi Zhou; Bo Huang; Yulong Wang (Pesticide Biochemistry and Physiology, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Scandium enrichment in the weathering crust of Emeishan basalt, Dali: geochemical abundance, occurrence states, and pre-concentration potential - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Coffee intercropping reduces soil N2O and N2 emissions: Empirical test and meta-analysis - Ronghua Li; Nanke Ma; Yue Shi; Hao Sun; Ziman Yang; Yun Zhou; Liyin Li; Syed Turab Raza; Tao Ye; Li Rong; Leqi Fang; Zhe Chen; et al. (Journal of Environmental Management, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

Development and validation of an LC-MS/MS method for a sensitive quantitation of livestock and poultry meat allergens - Shupeng Yang; Yingnan Shencheng; Yumeng Zhao; Meizhen Zhou; Mohamed F. Abdallah; Yanan Gao; Min Gao; Rong Zhang; Shuyan Liu; Yi Li (Food Chemistry, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

A biodegradable cellulose-based ionic conductor for sustainable and high-safety quasi-solid-state sodium batteries - Yuejing Zeng; Rong Tang; Minghui Chen; Yaqi Zhang; Wei Li; Huiya Yang; Ruilai Ye; Xue Li; Yang Yang; Jinbao Zhao (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Orbital-engineering-enabled electrified ferrocene–FeOOH membrane for effective flow-through organoarsenic mineralization and arsenic sequestration - Xin Gao; Qian Li; Rong Chen; Xuefeng Liu; Lin Yang; Yongshen Hou; Hao Sun; Yanbiao Liu; Haitao Wang; Yi Wang (Chemical Engineering Journal, 2025)

Development stage of biocrusts regulates soil carbon mineralization and its hydrothermal sensitivity in a temperate desert ecosystem - Xiaojun Li; Haotian Yang; Dinghai Zhang; Jingyao Sun; Rong Yang (CATENA, 2025)

ZxSAUR15 regulates root growth and abiotic stress tolerance: from genome-wide characterization of SAUR genes in Zygophyllum xanthoxylum to functional validation - Chunli Liu; Mengzhan Li; Yuting Yang; Rong Chai; Li Wei; Hongju Yin (Plant and Soil, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Crop diversification improves productivity and soil health by regulating fungal diversity - Rui Li; Zhibin He; Peng He; Rong Yang; Dengke Ma; Yuan Li; Yangzhou Xiang; Weihao Sun; Xi Zhu; Zhixin Zhang (Soil and Tillage Research, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

The late Eocene pine seed cones from Mangkang Basin, southeastern Xizang (Tibet) and their biogeographic significance - Xuan-Rong Yao; Yi Gao; Ren-Dan Yang; Jiang-Bo Meng; Shu-Feng Li; Tao Su (Palaeoworld, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Photochemical oxidation mechanisms and toxicity evolution of photostable atrazine during sunlight/free chlorine process - Xiaoyan Y. Ma; Xiaoru Li; Haixiang Jia; Jiahui Kho; Jiangyong Hu; Shengjiong Yang; Rong Chen; Xiaochang C. Wang; Nan Wang (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Unraveling the source-terminal PAH pollution from coal chemical wastewater in the Yellow River Basin via molecular fingerprint concentration analysis - Rong Li; Quanzhen Liu; Xiong Xu; Yongchang Xie; Lihua Lin; Mengru Yang; Donghong Wang (Environmental Pollution, 2025)

Meso–Cenozoic exhumation history of Northeast Asia and its connections with tectonic and climatic factors - Hongtao Wang; Shichao Li; Rong Yang; Xiaopeng Yang; Fangbin Liu; Zheren Zhao (Earth-Science Reviews, 2025)

GO-enhanced polyurethane phase change materials with triple dynamic bonds: Oxime-urethane, coordination and hydrogen bonds - Rong Huang; Fu Zhao; Yongsheng Li; Zhuoni Jiang; Fangfang He; Kai Zhang; Zhengguo Chen; Guansong He; Wenbin Yang (Chemical Engineering Journal, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Insights into mixotrophic metabolisms of anammox core consortia for rapid biofilm formation under low-oxygen conditions - Jiaqi Zhang; Hao Zhang; Ziyu Xu; Dayong Zhang; Guohao Yang; Quan Zhang; Rong Li; Xiao-Ming Ji (Chemical Engineering Journal, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Research on quantitative monitoring of new meteorological-agricultural compound drought characteristics - Yang Yu; Lei Zhou; Wenliang Wang; Rong Tian; Jingxin Zhang; Senmiao Hu; Qingzhu Zhang; Yalan Li (Theoretical and Applied Climatology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Network pharmacology, molecular docking, and molecular dynamics simulation analysis reveal the molecular mechanism of halociline against gastric cancer - Xiangru Zha; Rong Ji; Yang Li; Rong Cao; Songlin Zhou (Molecular Diversity, 2025)

Similarity analysis and verification of the relationship between resistance coefficients in porous media of different scales: Focusing on slatted floor - Qizhi Yang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Xi Bai; Zhiru Hu; Jie Chai; Yong Wang; Guoqiang Zhang (Biosystems Engineering, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

The effect of DHN melanin synthesis mediated by trihydroxynaphthalene reductase Aabrm2 on the cell membrane, cell wall integrity, and toxin synthesis of Alternaria alternata - Rong Li; Li Li; Xiwang Wang; Qianqian Jiang; Yuanping Nan; Yang Bi; Yongcai Li (Physiological and Molecular Plant Pathology, 2025)

Nonlinear numerical investigation and performance analysis of an oscillating-body wave energy converter integrated with a floating breakwater - Xiongbo Zheng; Wenbin Lai; Jialong Li; Sizhang Rong; Hongkun Yang (Ocean Engineering, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Effects of mulches on greenhouse gas emissions and soil microbial communities in cabbage production - Rong Liang; Lei Mei; Xuelian Fan; Jiangxing Wu; Mouliang Xiao; Yongfu Li; Jina Ding; Li Wang; Jaloliddin Shavkiev; David R. Chadwick; Davey Jones; Zhaofeng Yuan; et al. (Journal of Hazardous Materials, 2025)

Multifunctional microbial inoculation regulates compost product microbiomes, with implications for improving crop health and yield - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Xingxiang Deng; Guixian Xie; Gongwen Luo (Journal of Cleaner Production, 2025)

Long-term cadmium stress influenced the immune response of Pardosa pseudoannulata by modulating its gut microbiota and hemolymph metabolome - Jinjin Li; Yuan-de Peng; Rong Zhou; Jie Peng; Qingling She; Xinyi Yang; Juan Wang; Zhi Wang; Qisheng Song (Journal of Environmental Sciences, 2025)

Creep characteristics and damage mechanisms of rock in the plateau tunnel: Insights from acoustic emission and energy evolution - Yanzhe Li; Chuanxin Rong; Zhensen Wang; Yang Wang (Geomechanics for Energy and the Environment, 2025)

Evaluation of probiotic properties of lactic acid bacteria and physicochemical characteristics of fermented jujube (Ziziphus jujuba Mill.) polysaccharides - Rong Wang; Shufan Xie; Fei Li; Lanjian Qin; Jianming Ye; Jiaqi Chen; Xiao Yang; Yunlu Wei (Food Bioscience, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Corrigendum to “Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression” [Toxicology 514 (2025) 154129] - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Overexpression of the Nitraria sibirica Pall. H+-pyrophosphatase gene NsVP1 improves Arabidopsis salt tolerance - Xihong Wan; Xiuyan Yang; Rongfeng Duan; Rong Li; Yongxin You; Huaxin Zhang; Shuaihui Zhang; Pengyu Ying; Huilong Zhang (Plant Science, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Regulatory measures for mitigating physical and mental health impacts in aerospace environment: A systematic review - Rong Liang; Jing Gao; Xiaohui Liu; Xinyao Li; Haonan Chang; Rongdian Yang; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2025)

Electro-conductive nylon mesh assisted electro-chemical membrane bioreactor process (EMBR) for municipal wastewater treatment - Songhua Li; Yisong Hu; Jinzhuo Shi; Wenqian Xiao; Yuan Yang; Rong Chen (Journal of Water Process Engineering, 2025)

Overexpression of anthocyanin activator LrAN2 improving black goji berry (Lycium ruthenicum) tolerant to cadmium stress - Peiyan Ai; Zhiqiang Wang; Yan Li; Rong Yang; Biao A; Yixin Jia; Yuan Zong; Ying Wang; Shaohua Zeng (Journal of Hazardous Materials, 2025)

Removal of aqueous As(Ⅴ) by biochar stabilized green synthesized iron nanoparticles: Optimization, mechanism and DFT insights - Xueping Li; Hong Chen; Kun Rong; Qi Gao; Jianchao Jin; Shilai Yi; Qian Yang; Chunlong Sun; Ruimin Li; Zhenjiang Yin; Zaiwang Zhang (Journal of Environmental Chemical Engineering, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Mechanisms of integrated porous biochar and Fe3O4 in modulating carbon emissions and humification in co-composting of cattle manure and wheat stalk - Xu Yang; Cong Shao; Miaoqu Wang; Wanqiang Zhang; Wenxin Zhang; Haoduo Bai; Jie Zhang; Cleophas Achisa Mecha; Rong-Hua Li (Chemical Engineering Journal, 2025)

Quantitative modeling of substrate velocity effects on deposition efficiency and precursor consumption in spatial ALD - Geng Ma; Zhaojie Wang; Yuan Gao; Zoushuang Li; Xuewei Jiang; Yanwei Wen; Bin Shan; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Chemical constituents of the deep-sea-derived fungus Purpureocillium lilacinum XIA-18 and their chemotaxonomic significance - Bao-Fu Li; Yuan Wang; Zheng-Biao Zou; Rong Chao; Tai-Zong Wu; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Global synthesis on the responses of microbial- and plant-derived carbon to conservation tillage - Yalin Yu; Li Li; Jinkang Yang; Yinan Xu; Ahmad Latif Virk; Jie Zhou; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Plant and Soil, 2025)

IFN-γ2 enhances proliferation and differentiation of muscle cells: a novel target of natural grass feeding mode improving muscle quality in grass carp (Ctenopharyngodon idella) - Huijie Chen; Yin Wang; Jieya Liu; Qiushi Yang; Jiamin Lu; Tingting Xu; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Deep reinforcement learning algorithm incorporating problem characteristics for dynamic multi-objective permutation flow-shop scheduling problem - Yuan-Yuan Yang; Bin Qian; Rong Hu; Zuocheng Li; Zi-Qi Zhang; Huai-Ping Jin; Jian-Bo Yang (Swarm and Evolutionary Computation, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Spatio-temporal dynamic characteristics of the substitution effect of ride-hailing travel and its multi-activity network: a case study of Chengdu - Zhicheng Zheng; Yang Li; Peijun Rong; Lijun Zhang; Yaochen Qin; Gangjun Liu (Journal of Transport Geography, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Ant colony-inspired cooperative control of multi- magnetorheological dampers system for coupled vibration mitigation of spatial irregular structures - Yang Yang; Zhao-Dong Xu; Xing-Huai Huang; Yao-Rong Dong; Jun Dai; Yuan-Jin Li (Engineering Structures, 2025)

Shaking table tests and numerical studies on a robust enhanced gas-spring nonlinear energy sink for seismic response control of electricity transmission tower-line systems - Kunjie Rong; Chenyu Zhang; Li Tian; Meng Yang; Haomiao Chen; Junrong Gong (Engineering Structures, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

A hybrid coupled model for the tropical Pacific constructed by integrating ROMS with a statistical atmospheric model - Rong-Hua Zhang; Wenzhe Zhang; Yang Yu; Yinnan Li; Feng Tian; Chuan Gao; Hongna Wang (Journal of Oceanology and Limnology, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Pp07886, a glycoside hydrolase family 5 protein from Pythium porphyrae, is a required virulence factor and induces host disease resistance - Huichao Yang; Zhaolan Mo; Peiwen Weng; Yongwei Yan; Lei Tang; Xiaojun Rong; Jie Li (Algal Research, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Multi-stage dolomitization controlled by sedimentary facies and basement faults: Insights from the Middle Permian Maokou Formation of the Eastern Sichuan Basin, SW China - Rong Yang; Xiyan Yang; Yang Li; Cunhui Fan; Yue Li; Zisang Huang; Fei Huo; Xingzhi Wang; Xiangyu Fan (Marine and Petroleum Geology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Recent advances and future research directions in the study of land-atmosphere interaction in northern China since the beginning of the 21st century - Qiang Zhang; Rong Wang; Ping Yue; Hongyu Li; Sheng Wang; Jian Zeng; Liang Zhang; Zesu Yang; Suping Wang; Jie Zhang; Liang Qiao; Hongli Zhang; et al. (Science China Earth Sciences, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Risk Assessment of International Seabed Mining Implementing the Analytic Hierarchy Process - Xinyu Ma; Yejian Wang; Kehong Yang; Jinrong Li; Yan Li; Dongsheng Zhang; Rong Wang; Yinxia Fang (Journal of Marine Science and Engineering, 2025)
The international seabed area (“the Area”) harbors abundant metal mineral resources that are critical to address global metal supply–demand and sustainable development. However, exploitation of mineral resources in the Area faces complex risks spanning politics, economy, technology, science, environment, society, industry, and law. No commercial-scale deep-sea mining operations have been conducted to date. Systematic risk identification and prioritization can inform strategic planning for stakeholders. This study employs literature analysis and an 80-expert questionnaire to identify key risk factors affecting mineral exploitation in the Area. Using the Analytic Hierarchy Process (AHP), we quantitatively assess the relative importance and weightings of these risks. Our results indicate that Level 1 risk groups prioritize (1) policy and public opinion risk, (2) extended continental shelf (ECS) delineation risk, (3) high sea marine protected areas (HSMPAs) establishment risk, and (4) mining area economic value risk. The five most critical Level 2 risk factors are (i) policy changes in contractor states, (ii) ECS-mining area boundary conflicts, (iii) environmental provisions in exploitation regulations at the international seabed (ER), (iv) ER implementation delays, and (v) mineral resource uncertainty. These findings provide actionable insights for contractors, policymakers, and stakeholders to optimize decision making in deep-sea mining projects.

Multiple snapshot RFI localization fusion algorithm based on Gaussian process regression - Yang Zhao; Rong Jin; Yinan Li; Haofeng Dou (International Journal of Remote Sensing, 2025)

Genomic and antimicrobial resistance profiles of Clostridium perfringens isolated from pets in China - Mingjin Fang; Yuan Yuan; Xin Tian; Ying Liu; Ke Wu; Yanyan Zhu; Likun Zhang; Edward M. Fox; Ruichao Li; Li Bai; Menghan Li; Guerrino Macori; et al. (Veterinary Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Reduced mixed Ni-Co-Al metal oxide catalysts with rich oxygen vacancy derived from layered double hydrotalcite for selective hydrogenation of furfuryl alcohol to 1,5-Pentanediol - Nan Xi; Qiwang Li; Yi Chen; Ruixi Bao; Qinglian Wang; Yixiong Lin; Jun Yue; Rong Wang; Chen Yang; Wang Yin; Ting Qiu (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Dual-mode sensing platform based on an iodide ion synergistic covalent triazine frameworks (CTFs) for point-of-care testing (POCT) of acetylcholinesterase - Yanyue Chen; Huan Cheng; Hongling Tao; Jiali Liu; Yulong Li; Qiu-Xia Li; Tong Yang; Shuang Meng; Yunhui Yang; Rong Hu (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Internal Tide Generation and Propagation in the Sulu Sea Under the Influence of Circulation - Yuhao Rong; Yunchao Yang; Chao Wang; Heng Li; Jiahui Li; Xiaodong Huang (Journal of Marine Science and Engineering, 2025)
The Sulu Sea has active internal tides (ITs) and basin-scale circulation. This study, for the first time, employs three-dimensional simulations to investigate the effects of the Sulu Sea circulation on IT generation and propagation. Results reveal that the cyclonic circulation can enhance the semi-diurnal and diurnal IT energy conversion in the Sulu Archipelago by approximately 17% and 77%, respectively, compared to those without circulation for semi-diurnal ITs (4.36 GW) and diurnal ITs (2.76 GW). This different increase portion between semi-diurnal and diurnal ITs is attributed to different influences of circulation on the positive and negative conversion rates for semi-diurnal and diurnal ITs. Energy budget analysis indicates that circulation increases the proportion of dissipation near source regions from 88% (90%) to 94% (93%) and reduces the proportion of energy flux radiation from 12% (10%) to 6% (7%) for semi-diurnal (diurnal) ITs. The ray-tracing results indicate that the cyclonic circulation induces significant westward refraction of IT rays by modulating IT speeds in counter-current/co-current regions. Further sensitive experiments reveal that circulation-induced stratification weakens the refraction, whereas the background currents strengthen it, with the latter dominating. These findings advance our understanding of the IT behaviors in the Sulu Sea under the modulation of circulation.

A high-efficiency lettuce quality detection system based on FPGA - Zhenzhong Wang; Tongge Li; Rong Du; Ning Yang; Jianfeng Ping (Computers and Electronics in Agriculture, 2025)

Potential role of Mc3r and Mc4r in ovarian metabolism and development in female red crucian carp (Carassius auratus red var.) - Faxian Yu; Lu Huang; Xinxin Yu; Shuxin Zhang; Shengnan Li; Rong Zhou; Wenjing Tao; Lanying Yang; Min Tao; Qizhi Liu; Shaojun Liu (Aquaculture, 2025)

AaRgs2 regulates growth and virulence of Alternaria alternata by maintaining reactive oxygen species (ROS) balance - Yuanping Nan; Miao Zhang; Yangyang Yang; Rong Li; Qianqian Jiang; Xuexue Wang; Yongcai Li; Yang Bi (Postharvest Biology and Technology, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Source and variability of formaldehyde in the Fenwei Plain: An integrated multi-source satellite and emission inventory study - Liang Li; Keqin Duan; Yuyao Wu; Junhua Yang; Ting Yang; Peihong Shi; Rong Chen (Journal of Environmental Sciences, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Precipitation changes reshape desert soil microbial community assembly and potential functions - Kai Sun; Rong Yang; Jiliang Liu; Wenzhi Zhao; Xiaojun Li; Yongzhen Wang; Shujun Song (Environmental Research, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Effects of different concentrations of N-acetylcysteine on the sperm quality, antioxidant enzyme activity, and antioxidant gene expression of cryopreserved goat semen - Xiaodong Wang; Jinhong Luo; Maosheng Cao; Yonghong Ju; Qingmeng Long; Rong Yang; Quan Ji; Guangbin Zhou; Junwei Zhang; Ruiyang Li; Xiang Chen (Theriogenology, 2025)

Reticulophagy promotes EMT-induced fibrosis in offspring’s lung tissue after maternal exposure to carbon black nanoparticles during gestation by a m5C-dependent manner - Zhe Du; Qingping Liu; Mengruo Wang; Yifu Gao; Qi Li; Yizhe Yang; Tianyu Lu; Lei Bao; Yaxian Pang; Haijun Wang; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Development of QuEChERS based on the Z-Sep+and DLLME method for analysis of PBDEs in chicken eggs by GC–MS/MS - Xiaojing Li; Rong Yang; Zhijun Bai; Pingsheng Gan; Tao Zeng; Miao Liu; Jun Yuan (Food Chemistry, 2025)

Auxin regulates leaf senescence and nitrogen assimilation to promote grain filling in maize (Zea mays L.) - Na Jiang; Peng Wang; Zhiqi Yang; Changwei Li; Yixiang Xia; Xiangmin Rong; Yongliang Han; Lan Yang (Field Crops Research, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Crop straw converted to biochar increases soil organic carbon but reduces available carbon - Li Li; Jinkang Yang; Yalin Yu; Awais Shakoor; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (European Journal of Agronomy, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Effects of crop rotation on plant- and microbial-derived carbon within particulate and mineral fractions in paddy soils - Yalin Yu; Ningxuan Zhu; Ying Ren; Menghan Dong; Guofeng Sun; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Agriculture, Ecosystems & Environment, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Soil bacterial community composition but not alpha diversity altered along a gradient of Spartina alterniflora invasion on the coast of Yellow Sea, China - Li Yang; Yue Peng; Shuang Wang; Chenxuan Rong; Huice Dong; Hongshan Li; Baoming Ge (Frontiers in Marine Science, 2025)
Introduction Spartina alterniflora invasion may alter the characteristics and functions of the coastal wetland ecosystems. Previous studies have shown that invasion changes the biogeochemical processes and microbial diversity in marsh ecosystems; however, knowledge of the changes in bacterial communities and their function at different soil depths during invasion remains limited. Methods In the present study, we investigated S. alterniflora invasion on the dynamic changes of soil bacterial communities using Illumina MiSeq sequencing analyses of 16S rRNA at different soil depths (i.e., 0–10, 10–20, and 20–40 cm) during the invasive process (i.e., 1, 4, 7, and 12 years), as well as the potential correlations between soil physicochemical characteristics and enzyme activities. Results The invasion of S. alterniflora did not significantly affect soil bacterial alpha diversity or the functional profiles at the first and second levels of the Kyoto Encyclopedia of Genes and Genomes (KEGG). Furthermore, no significant changes were observed across different soil depths. However, the relative abundances of Chloroplast and Alphaproteobacteria increased from 3.03% and 5.05% in bare mudflat to 13.61% and 8.95% in the 12-year-old S. alterniflora invaded soil, respectively, whereas those of Deltaproteobacteria, Acidimicrobiia, and Bacilli decreased after S. alterniflora invasion for approximately 12 years. The relative abundances of soil bacteria varied with soil depth. Total phosphorus, carbon-to-nitrogen ratio, total carbon, and catalase activity were the key factors affecting soil bacterial community composition. Discussion The soil physicochemical characteristics changes caused by invasion may temporarily enhance soil fertility, they can lead to long-term wetland degradation through changed biological community and altered nutrient dynamics. This study provides a comprehensive understanding of the dynamic changes in bacterial communities, soil physicochemical characteristics, and enzyme activities during S. alterniflora invasion on coastal wetlands.

Numerical evaluation on spray cooling to mitigate heat stress in cattle using computational fluid dynamics - Ruimin Yang; Wenqi Zhang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kai Liu; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2025)

Vision transformer based classification of sewer defects weighted loss model - Chunhou Ji; Zhiqiang Xie; Rong Li; Zhibing Yang; ZhiQun Hou (Tunnelling and Underground Space Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhancing anammox performance under starvation stress: The role of pyrite in regulating nitrogen and sulfur metabolism - Huiying Sui; Na Zhang; Baoyong Zhang; Zunqing Wen; Ruiyan Zhang; Huan Yang; Zengjin Li; Rong Xue (Journal of Water Process Engineering, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

BCP4: A novel antimicrobial peptide with potent efficacy against Bacillus cereus in rice porridge - Weihong Tao; Wenjie Li; Ritian Jin; Duo Liang; Wuyin Weng; Rong Lin; Shen Yang (International Journal of Food Microbiology, 2025)

Amine-impregnated elastic carbon nanofiber aerogel templated by bacterial cellulose for CO2 adsorption and separation - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2025)

Effect of magnetic field-assisted thawing on the quality and microstructure of Portunus trituberculatus meat - Rong Shi; Zhongqi Sun; Xuemei Yu; Huamao Wei; Gaoshang Li; Wenge Yang (Food Research International, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Zwitterionic polymer as binder for LiFePO4 cathodes in lithium-ion batteries - Meng Yang; Zhuolin Rong; Xuewei Li; Bing Yuan; Wangqing Zhang (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Linker Histone H1.4 Inhibits the Growth, Migration and EMT Process of Non-Small Cell Lung Cancer by Regulating ERK1/2 Expression - Qian Chen; Mengqi Yang; Xinyue Duan; Jie Zhang; Fan Shi; Rong Chen; Yong Li (Biochemical Genetics, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Occurrence characteristics and factors that influence shale oil in the Jurassic Lianggaoshan Formation, northeastern Sichuan Basin - Xuefeng Bai; Xin Wang; Min Wang; Junhui Li; Shuangfang Lu; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Youzhi Wang (Marine and Petroleum Geology, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Bacillus subtilis fermented shrimp waste isolated peptide, PVQ9, and its antimicrobial mechanism on four Gram-positive foodborne bacteria - Weihong Tao; Wenjie Li; Jude Juventus Aweya; Rong Lin; Ritian Jin; Duo Liang; Zhongyang Ren; Shen Yang (Food Microbiology, 2025)

Prevalence and genomic characteristics of becAB-carrying Clostridium perfringens strains - Mingjin Fang; Yuan Yuan; Edward M. Fox; Ke Wu; Xin Tian; Likun Zhang; Hang Feng; Ruichao Li; Li Bai; Xinglong Wang; Zengqi Yang; Rong Zhang; et al. (Food Microbiology, 2025)

Effects of exposure to 17α-methyltestosterone on hepatic lipid metabolism in Gobiocypris rarus - Tongyao Li; Zijun Xiong; Weiya Rong; Qiong Yang; Yue Chen; Haiyan Zhao; Qing Liu; Jing Song; Weiwei Wang; Yu Liu; Xianzong Wang; Shaozhen Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Enhanced performance and stability of sulfite/sulfide-assisted photocatalytic fuel cell with CdS@TNTs/Ti mesh photoanode - Yuxin Liu; Youxu Yu; Jinwang Li; Xun Zhu; Dingding Ye; Yang Yang; Zhefei Pan; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2025)

Lithium directed growth triggered by vertical interface activity gradient framework enabling long-life Li metal anode - Chenyi Sun; Li Gao; Wanling Rong; Yinghui Yang; Yanwen Bai (Chemical Engineering Journal, 2025)

Methoxyflavone glucosides and caffeoyl phenylethanoid glycoside from Lysionotus pauciflorus: their structures and anti-ferroptosis activity - Rena Takizawa; Tomoyo Minamizono; Daisuke Tsuji; Xiao-Jie Yan; Feng-Lai Lu; Xue-Rong Yang; Dian-Peng Li; Reiko Akagi; Yoshiki Kashiwada; Naonobu Tanaka (Journal of Natural Medicines, 2025)

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.